Lipotoxicity-induced STING1 activation stimulates MTORC1 and restricts hepatic lipophagy. Issue 4 (3rd April 2022) - Liu, Kunpeng; Qiu, Dongbo; Liang, Xue; Huang, Yingqi; Wang, Yao; Jia, Xin; Li, Kun; Zhao, Jingyuan; Du, Cong; Qiu, Xiusheng; Cui, Jun; Xiao, Zhendong; et al.
ABSTRACT: Lipid accumulation often leads to lipotoxic injuries to hepatocytes, which can cause nonalcoholic steatohepatitis. The association of inflammation with lipid accumulation in liver tissue has been studied for decades; however, key mechanisms have been identified only recently. In particular, it is still unknown how hepatic inflammation regulates lipid metabolism in hepatocytes. Herein, we found that PA treatment or direct stimulation of STING1 promoted, whereas STING1 deficiency impaired, MTORC1 activation, suggesting that STING1 is involved in PA-induced MTORC1 activation. Mechanistic studies revealed that STING1 interacted with several components of the MTORC1 complex and played an important role in the complex formation of MTORC1 under PA treatment. The involvement of STING1 in MTORC1 activation was dependent on SQSTM1, a key regulator of the MTORC1 pathway. In SQSTM1-deficient cells, the interaction of STING1 with the components of MTORC1 was weak. Furthermore, the impaired activity of MTORC1 via rapamycin treatment or STING1 deficiency decreased the numbers of LDs in cells. PA treatment inhibited lipophagy, which was not observed in STING1-deficient cells or rapamycin-treated cells. Restoration of MTORC1 activity via treatment with amino acids blocked lipophagy and LDs degradation. Finally, increased MTORC1 activation concomitant with STING1 activation was observed in liver tissues of nonalcoholic fatty liver disease patients, which provided clinical evidence for the involvement of STING1 in MTORC1 activation. In summary, we identified a novel regulatory loop of STING1-MTORC1 and explain how hepatic inflammation regulates lipid accumulation. Our findings may facilitate the development of new strategies for clinical treatment of hepatic steatosis. Abbreviations : AA: amino acid; ACTB: actin beta; cGAMP: cyclic GMP-AMP; CGAS: cyclic GMP-AMP synthase; DEPTOR: DEP domain containing MTOR interacting protein; EIF4EBP1: eukaryotic translation initiation factor 4E binding protein 1; FFAs: free fatty acids; GFP: green fluorescent protein; HFD: high-fat diet; HT-DNA: herring testis DNA; IL1B: interleukin 1 beta; LAMP1: lysosomal associated membrane protein 1; LDs: lipid droplets; MAP1LC3: microtubule associated protein 1 light chain 3; MAP1LC3B: microtubule associated protein 1 light chain 3 beta; MEFs: mouse embryonic fibroblasts; MLST8: MTOR associated protein, LST8 homolog; MT-ND1: mitochondrially encoded NADH: ubiquinone oxidoreductase core subunit 1; mtDNA: mitochondrial DNA; MTOR: mechanistic target of rapamycin kinase; MTORC1: MTOR complex 1; NAFL: nonalcoholic fatty liver; NAFLD: nonalcoholic fatty liver disease; NASH: nonalcoholic steatohepatitis; NPCs: non-parenchymal cells; PA: palmitic acid; PLIN2: perilipin 2; RD: regular diet; RELA: RELA proto-oncogene, NF-kB subunit; RPS6: ribosomal protein S6; RPS6KB1: ribosomal protein S6 kinase B1; RPTOR: regulatory associated protein of MTOR complex 1; RRAGA: Ras related GTP binding A; RRAGC: Ras related GTP binding C; SQSTM1: sequestosome 1; STING1: stimulator of interferon response cGAMP interactor 1; TBK1: TANK binding kinase 1; TGs: triglycerides; TREX1: three prime repair exonuclease 1.